Revisiting the nexus of Internet and political participation: a longitudinal study of environmental petition in China. Issue 3 (3rd July 2022) - Lu, Shuning; Lin, Tse-min
ABSTRACT: The political implications of the Internet remain as a long-debated question. To clarify this puzzle, this study draws on insights from political opportunity structure theory and three prompts for political action in the digital media environment to examine how the development of the Internet is related to environmental petition, a type of citizen-initiated political activity in the state realm in China. Using government statistics from multiple sources, we conducted time-series cross-sectional analyses to estimate the impacts of Internet penetration on environmental petition in China's 31 provinces over a 13-year period (2003–2015). The findings show that Internet penetration had a long-term negative effect on visit petition but a positive one on letter petition. Implications of the findings and future research directions are discussed.